Chemoselective preparation of 1,1-diacetates from aldehydes, mediated by a Keggin heteropolyacid under solvent free conditions at room temperature - Romanelli, Gustavo Pablo (2007)
A simple, general and efficient method has been developed for the conversion of aldehydes to 1,1-diacetates using acetic anhydride, a catalytic amount of non commercial Keggin heteropolyacid (H6 PalMo11O40) (1% mol) in solvent free conditions at room temperature. Aromatic and aliphatic, simple and conjugated aldehydes were protected with excellent yields.